Histamine-2 Receptor Antagonists and Proton Pump Inhibitors: Efficacy and drug prediletion in Stress Ulcer prophylaxis in patients admitted to the Pediatric Oncology ICU at Uopeccan Hospital (Research, Society and Development, 2024)
Objective: To analyze and obtain results for Stress Ulcer prophylaxis with Proton Pump Inhibitors and Histamine-2 Receptor Antagonists in a patient in the pediatric ICU. The objective of this study reviews the predilection, existence of criteria and prophylactic effectiveness of both. Methods: It is developed from a retrospective observational study composed of medical records/data collection from patients in the Pediatric Intensive Care Unit at Hospital Uopeccan of Cascavel, between January 2012 and January 2022. Data relating to gender, age, diagnosis, reason for hospitalization, length of stay in the ICU and choice of gastric protector. Results: 43 cases of patients admitted to the ICU during the stipulated period were analyzed. Of these, the average age of patients in the research carried out was 4 years and 5 months, with 39.53% (n=17) female and 60.46% (n=26) male with an average hospitalization of approximately 10,6 days. Approximately 94.28% (n=33) of patients received some type of prophylactic, and within this percentage, 91.42% (n=32) of cases used PPI, 2.85% (n=1) ARH2 and 5.71% (n=2) did not use any medication. Conclusion: Based on this study, it is possible to conclude that there is a lack of scientific evidence and comprehensive research related to Proton Pump Inhibitors (PPI) and Histamine 2 Receptor Antagonists (ARH2) in clinical practice. This information gap may represent a potential disadvantage for patients, given the lack of specific criteria for Stress Ulcer prophylaxis in Pediatric Intensive Care Centers.